Prototype of student degree classification - Rosyusjuliza, Yusoff (2006)
Degree Classification normally classified after the student finished their study.The student degree classification forecasting is important to classify student degree class before the learning process ended.Therefore,the "Prototype of Student Degree Classification Forecasting (POSDC)" is the suggestion prototype that will solve the manual system used currently.The purpose of this prototype is to forecast student degree class by their student id or name.The forecasting result calculated based on their previous CGP A and credit hours countered for each semester.The student will be classified to 4 classes which are First Class Honours,Upper SeconddClass Honours,Lower Second-Class Honours and Third Class Honours.There are two users of this prototype which are Academic Advisor and REA staffs.The technique that used for this prototype is Fuzzy Logic Technique which is fuzzy rules because it is the most suitable technique applied for forecasting and the result shows that fuzzy rules also is a good technique applied for degree classification forecasting.